Improving access to Indigenous medicine for patients in hospital-based settings: a challenge for health systems in northern Canada. Issue 2 (28th January 2019) - Redvers, Nicole; Marianayagam, Justina; Blondin, Be'sha
ABSTRACT: In this commentary, we argue that Indigenous patients in the Northwest Territories (NWT) have a right to access traditional medicine and related practitioners as a part of the continuum of medical care. Indigenous people make up over half of the NWT population, spread over vast geographic areas with representation from First Nations, Inuit and Métis (FNIM) people. Ensuring barrier-free access to traditional medicine and providers in a culturally respectful environment is a challenge that requires structural transformation in the territorial health system. The ongoing transmission of knowledge about Indigenous traditional medicine in Northern Canada and the collective survival of Northern peoples is a testament to the applicability of traditional medicines in a self-determined wellness system. Through a discussion of the barriers to policy development and implementation, this commentary aims to elevate Indigenous perspectives and offer recommendations for integrating traditional medicines into Northern health systems.